Applying cognitive theory of multimedia learning principles to augmented reality and its effects on cognitive load and learning outcomes - Vito Candido; Alberto Cattaneo (Computers in Human Behavior Reports)
In the last decade, the use of augmented reality as a learning support tool has been extensively researched, largely due to the proliferation of augmented reality-compatible smartphones. However, findings related to cognitive load levels remain mixed, with studies reporting both an increase and a decrease in cognitive load while using augmented reality when compared to traditional media. This study investigates the influence on cognitive load and learning outcomes of applying cognitive theory of multimedia learning principles to augmented reality applications. Application design plays a pivotal role in determining cognitive load levels, particularly extraneous load, yet cognitive theory of multimedia learning principles have been scarcely investigated in augmented reality contexts. A randomized experimental design was employed, in which 88 participants were assigned to one of three groups: augmented reality with a head-mounted display, hand-held augmented reality, or video (control group). The educational materials for all conditions were designed according to the principles of the cognitive theory of multimedia learning. Learning outcomes were assessed through retention and transfer tasks following an activity involving a Tangram game. Bayesian analyses provided evidence for no difference in extraneous load levels between conditions. Regarding performance, the findings were inconclusive, showing evidence neither for difference nor equivalence between conditions in both retention and transfer tasks.This study supports the idea that the effectiveness of the cognitive theory of multimedia learning principles can be extended to augmented reality. The encouraging results on extraneous load levels require further investigation regarding performance.